2015
DOI: 10.1021/acs.bioconjchem.5b00091
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans in Tendon Physiology, Pathophysiology, and Therapy

Abstract: Although glycosaminoglycans constitute a minor portion of native tissues, they play a crucial role in various physiological processes, while their abnormal expression is associated with numerous pathophysiologies. Glycosaminoglycans have become increasingly prevalent in biomaterial design for tendon repair, given their low immunogenicity and their inherent capacity to stimulate the regenerative processes, while maintaining resident cell phenotype and function. Further, their incorporation into three-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 253 publications
0
46
0
Order By: Relevance
“…It has been suggested that force is transferred laterally between adjacent fibrils via proteoglycans and their associated GAG chains, including chondroitin‐ and dermatan‐sulfate (Scott & Thomlinson, ; Ryan et al . ). However, removing this complex in human tendon (Svensson et al .…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that force is transferred laterally between adjacent fibrils via proteoglycans and their associated GAG chains, including chondroitin‐ and dermatan‐sulfate (Scott & Thomlinson, ; Ryan et al . ). However, removing this complex in human tendon (Svensson et al .…”
Section: Introductionmentioning
confidence: 97%
“…The pathologic hallmark of tendon fibrosis is underlined by changes in the composition of interstitial extracellular matrix (ECM) 6 7 8 9 10 . This is associated with the failure of timely termination of key molecular processes in the normal healing cascades, presumably due to continuing presence of physical and biochemical triggers and regulators 11 .…”
mentioning
confidence: 99%
“…Though GAGs make up a small percent of native tendon tissue, their presence in tendon ECM serve to protect tendons against shear and compressive forces . Additionally, GAGs have been shown to play a role in collagen fibrillogenesis, fiber diameter, and mechanical integrity . Furthermore, increased expression of collagen I protein was observed to be qualitatively increased with cells grown on electrospun fibers after treatment with insulin or IGF‐1 when compared with the control basal group (Figure ).…”
Section: Resultsmentioning
confidence: 99%